ANALISIS PEMANFAATAN RASI BINTANG ORION SEBAGAI INDIKATOR ASTRONOMI DALAM PENENTUAN WAKTU SALAT ISYA PERSPEKTIF ILMU FALAK - Damayanti, Riska; Agus, Jasdar (Universitas Islam Negeri Alauddin Makassar, 2025)
This research is motivated by the importance of understanding prayer times not only based on digital schedules or hisab, but also through a visual approach to natural signs, one of which is through the appearance of constellations. Orion, as a very prominent and easily recognized constellation, was chosen in this study to analyze its potential as an indicator of Isha prayer time. Based on this background, the main problem in this study is